Genetic And Non-Genetic Factors Affecting Breeding Efficiency In Malvi Cows - Tomar, S.S.; Sharma, Harish; Singh , Ashok (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
Effects of period and season of first calving and inbreeding on breeding efficiency by Wilcox (BEW) and Tomar (BET) Methods were studied on 403 Malvi cows maintained at the Government Cattle Breeding Farm, Agar, District Shajapur (M.P.). The least squares means of BEW and BET were found to be 88.04±1.52 and 76.83±0.89 per cent, respectively. Both the breeding efficiency were significantly (P
Keywords: Malvi Cattle; inbreeding; breeding efficiency